Nonlinear optical properties and broadband ultrafast photonics application of 2D-zirconium tritelluride (ZrTe3). (February 2023) - Qiao, Junpeng; Ahmed, Safayet; Cheng, Ping Kwong; Fan, Ranran; Saleque, Ahmed Mortuza; Ivan, Md. Nahian Al Subri; Yu, Jialiang; Liu, Guangqiang; Feng, Sujuan; Tsang, Yuen Hong
Highlights: 2D ZrTe3 nanosheets were successfully prepared and characterized. The nonlinear properties of ZrTe3 nanosheets were studied through the OA Z-scan technique in 1.0 and 1.5 μm wavebands. ZrTe3 SAs-based ultrafast lasers at wavelengths of 1.0, 1.5 and 1.9 µm have been demonstrated for the first time. Abstract: Two-dimensional (2D) transition metal chalcogenides (TMCs) have lately attracted broad interest in advanced photonics field due to their tunable bandgap, high broadband absorption, and excellent nonlinear optical (NLO) performances. Among other TMCs, group-IV transition metal trichalcogenides (TMTs) are rarely investigated for the NLO applications. Zirconium tritelluride (ZrTe3 ) is a kind of group-IV TMTs that shows metallic behavior among TMTs materials. While several electrical properties of ZrTe3 have been studied recently, the research community is longing to explore NLO features of ZrTe3 . Herein, by using open aperture Z-scan method, the NLO properties of ZrTe3 -nanosheets are investigated. The admirable NLO characteristics of ZrTe3 are realized from the obtained highest nonlinear absorption coefficient value of −82.1 × 10 3 in 1 µm and −13.05 × 10 3 cm/GW in 1.5 µm. Moreover, broadband fiber optics ZrTe3 -based saturable absorbers (SAs) are prepared for the first time by depositing 2D-ZrTe3 nanosheets on a side-polished fiber. Following integration of these ZrTe3 -SAs into three distinct rare earth-doped fiber laser cavities, stable mode-locking pulses with pulse widths of 323 ps (1 µm), 751 fs (1.5 µm), and 1.2 ps (2 µm) are obtained, respectively. These findings indicate that the ZrTe3 can facilitate the exploration of 2D materials in nonlinear optics and ultrafast photonics applications.